Nutritional status of children in Alagoas state cities according to SISVAN - da Silva Lira, Mayara Cristina; Egito de Menezes, Rísia Cristina; Longo-Silva, Giovana; Araújo Oliveira, Maria Alice; Souza Oliveira, Juliana; Chagas Costa, Emília; Sá Leal, Vanessa; Asakura, Leiko (O Mundo da Saúde, 2017)
The aim of the study was to evaluate the nutritional status of children under five in the most populated municipalities of Alagoas, and to compare the results with the population referring in the Northeast of Brazil and all of Brazil, using data from SISVAN, 2013. The populations studied, according to the municipalities were 10,642, 4,351, 1,752, 803 and 3,207 children in Maceio, Arapiraca, Palmeira dos Indios, Rio Largo and União dos Palmares, respectively. For the northeast region, the total was 225,252 children and for Brazil, 527,243. The cross-sectional study used as outcome variables, stunting and overweight, the Body Mass Index/Age and Height/Age, respectively, according to the WHO classification. The stunting ranged from 9% to 15% in the cities studied. In Alagoas, Brazil, and the Northeast, prevalence was approximately 14%. Regarding the risk of overweight, prevalence rates were found between 16% to 20%. Overweight was approximately 13% and obesity from 7.6% to 12.8% in the municipalities of Alagoas. Brazil, Alagoas and the Northeast showed a prevalence for overweight from 17.1% to 19.5%. Excess weight showed high among children, in the evaluated areas without malnutrition has been eradicated. Therefore, the importance of SISVAN for the nutritional diagnosis and the implementation of health improvement policies of the population assisted by the SUS must be recognized.